Maritime green supply chain management: its light and shadow on the bottom line dimensions of sustainable business performance - Fernando, Yudi; Muhamad Fairuz, Ahmad Jasmi; Muhammad Shabir, Shaharudin (Inderscience Enterprises Ltd., 2019)
The objective of this paper is to investigate the effects of maritime green supply chain management (MGSCM) on sustainable business performance. This paper addresses the complex dimensions of ‘sustainability’ to be integrated into maritime supply chain activities with the existing green supply chain concept linking the concept with the extended bottom line dimensions of sustainable business operations. To achieve the objective, an online survey was administrated to various maritime supply chain companies in Malaysia. The findings confirmed that MGSCM practices indirectly facilitate sustainable economic, environmental, operational and social performance for these businesses. This paper presents practical suggestions for maritime practitioners that highlight the need to materialise green practices adoption in the maritime supply chain in the future.